PENGELOLAAN PIUTANG PERUSAHAAN SUB-SEKTOR PERKEBUNAN DI INDONESIA - MOHAMAD ADAM; TAUFIK .; EKA YENY SUTANTO (Program Studi Magister Manajemen FE Unsri, 2015)
This study aims to determine the management of accounts receivable in some of the plantation sub-sector companies and determine the position of the company by using the SWOT analysis and the BCG matrix. The sampling method uses is purposive sampling method. Based on sampling criteria, the samples were subjected to experiments are PT Astra Agro Lestari Tbk, BW Plantation Tbk, PP London Sumatra Indonesia Tbk, PT Sampoerna Agro Tbk, Salim Ivomas Pratama Tbk, and Bakrie Sumatera Plantations Tbk. This research uses a descriptive study based on secondary data obtained from the Indonesia Stock Exchange. Analysis of the data used is the accounts receivable ratio analysis. The ratio of receivables consist of accounts receivable turnover rate, the average amount of accounts receivable, and accounts receivable average collection. Each company SWOT analysis and the BCG matrix. The results showed that the average turnover rate of receivables PT Astra Agro Lestari Tbk is the fastest. Average accounts receivable collection BW Plantation Tbk is the fastest. The average amount of receivables Salim Ivomas Pratama Tbk is the greatest. BCG matrix results demonstrate that SIMP is a company with a market share position is relatively the most.